Optimization of extraction conditions for Cupressus torulosa essential oil using response surface methodology and chemical characterization by GC-MS (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
This study aims to optimize Cupressus torulosa essential oil (CTEO) extraction conditions using Response Surface Methodology (RSM) and analyze its chemical composition. A three-factor, three-level Box-Behnken Design (BBD) was employed to evaluate the effects of extraction time, material-to-liquid ratio (MLR), and drying period on essential oil yield. The optimized conditions—5.355 hours of extraction, a 16:1 MLR, and a 5.285-day drying period—resulted in a predicted yield of 1.121%. Gas Chromatography-Mass Spectrometry (GC-MS) analysis identified 31 compounds, comprising 91% of the total oil, with β-Caryophyllene (10.91%), Δ-3-carene (10.21%), Terpinen-4-ol (9.81%), and Caryophyllene oxide (9.15%) as major constituents. Statistical validation using ANOVA confirmed the significance of the model, with extraction time having the most notable effect on yield. These findings highlight the importance of optimizing extraction parameters to maximize yield and maintain essential oil quality.